2022
DOI: 10.1186/s12936-022-04060-6
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of asymptomatic malaria and seroepidemiological surveillance of seven districts in Gia Lai province, Vietnam

Abstract: Background Malaria elimination by 2030 is an aim of many countries in the Greater Mekong Sub-region, including Vietnam. However, to achieve this goal and accelerate towards malaria elimination, countries need to determine the extent and prevalence of asymptomatic malaria as a potential reservoir for malaria transmission and the intensity of malaria transmission. The purpose of this study was to determine the prevalence of asymptomatic malaria and seropositivity rate in several districts of Gia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…Overall results show that humoral antibodies against P. falciparum antigens were higher than P. vivax antigens. This finding is consistent with previous studies in low transmission settings in Tak Province in Northwestern Thailand ( Baum et al., 2016 ) and other areas in Southeast Asia, namely, Indonesia ( Surendra et al., 2019 ), Myanmar ( Edwards et al., 2021 ), and Vietnam ( San et al., 2022 ). The dominance in exposure to P. falciparum could be attributed to the timing of data collection, which mainly occurred after the transmission season.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Overall results show that humoral antibodies against P. falciparum antigens were higher than P. vivax antigens. This finding is consistent with previous studies in low transmission settings in Tak Province in Northwestern Thailand ( Baum et al., 2016 ) and other areas in Southeast Asia, namely, Indonesia ( Surendra et al., 2019 ), Myanmar ( Edwards et al., 2021 ), and Vietnam ( San et al., 2022 ). The dominance in exposure to P. falciparum could be attributed to the timing of data collection, which mainly occurred after the transmission season.…”
Section: Discussionsupporting
confidence: 93%
“…The relationship between age and seroprevalence rates was similar in all studied areas, increasing with age, peaking at 46–60 years, then decreasing with age. In addition, seroprevalence and SCRs were higher in the older age group, indicating that the age-specific antibody response reflects cumulative exposure or population behavioral differences ( San et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The serological investigation in the present study revealed that humoral antibodies against P. falciparum antigens were higher than P. vivax antigens (i.e., 58% and 10%, respectively). This finding is consistent with previously described levels in other countries in the Southeast Asia region with P. falciparum-P. vivax co-endemic, such as Thailand (79% and 40%) (Rahim et al, 2022), Vietnam (38% and 31%) (San et al, 2022), Myanmar (30% and 14%) (Edwards et al, 2021), and Indonesia (6.9% and 2.0%) (Surendra et al, 2019). The higher seropositivity from P. falciparum may be due to the fact that serological assay used was originally developed to detect responses to PfAMA-1 and PfMSP-1 19 antigens and thus may be more sensitive in detecting this species (Tadesse et al, 2017;Björkman et al, 2019;Edwards et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…The levels of HRP2 protein were measured in all RDT negative/LM positive samples and a random selection of RDT positive samples. Protein elution was conducted from 2 × 5 mm punch of DBS (equivalent to 11.2 μl of blood or 5.6 μl of plasma, [ 18 ]), with a final elution in 1120 μl of buffer (1/200) [ 19 ]. Quantitative ELISA-based detection was conducted using Quantimal™ CELISA Ultra-sensitive PfHRP2 Malaria (Cellabs, Australia) according to manufacturer’s instructions [ 20 ].…”
Section: Methodsmentioning
confidence: 99%